Comparation of The Transfer of Land Rights to The Description Deed of Inheritance Rights - Tania Wijayanti; Yudho Taruno Muryanto; M. Irnawan Darori (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
Marriages are carried out by mixed ethics, so it is very difficult to know whether there are ethnics of Chinese, foreign-Eastern or indigenous groups in a cpopulation. This study aims to determine the legal certainty of a certificate of inheritance for Indonesian citizens of Chinese descent. The research method used is normative juridical. The results of the research and the conclusions show that the notary is the only official authorized to make an authentic deed, namely a certificate of inheritance rights for Indonesian citizens of Chinese descent in accordance with Article 15 of the UUJNP. Comparison of Arrangements for Transfer of Land Rights to Deeds of Inheritance Rights of Chinese Descendants In ASEAN countries, namely Malaysia, that the distribution is contained in Article 6 of the Distribution Act 1958 jo. (Amendment) Act 1997 One of Article 6 (1), then in Turkey Article 35 of the Land Registry Law No 2644 / 1934my which gives foreigners the right to acquire land in Turkey and is subject to legal provisions governing restrictions and prohibitions.